Accounting for professionalism: an innovative point system to assess resident professionalism - Gary L. Malakoff; Catherine L. Payne; Lisa J. Staton; Victor O. Kolade; Mukta Panda (Greater Baltimore Medical Center, 2014)
Background: Professionalism is a core competency for residency required by the Accreditation Council of Graduate Medical Education. We sought a means to objectively assess professionalism among internal medicine and transitional year residents. Innovation: We established a point system to document unprofessional behaviors demonstrated by internal medicine and transitional year residents along with opportunities to redeem such negative points by deliberate positive professional acts. The intent of the policy is to assist residents in becoming aware of what constitutes unprofessional behavior and to provide opportunities for remediation by accruing positive points. A committee of core faculty and department leadership including the program director and clinic nurse manager determines professionalism points assigned. Negative points might be awarded for tardiness to mandatory or volunteered for events without a valid excuse, late evaluations or other paperwork required by the department, non-attendance at meetings prepaid by the department, and inappropriate use of personal days or leave. Examples of actions through which positive points can be gained to erase negative points include delivery of a mentored pre-conference talk, noon conference, medical student case/shelf review session, or a written reflection. Results: Between 2009 and 2012, 83 residents have trained in our program. Seventeen categorical internal medicine and two transitional year residents have been assigned points. A total of 55 negative points have been assigned and 19 points have been remediated. There appears to be a trend of fewer negative points and more positive points being assigned over each of the past three academic years. Conclusion: Commitment to personal professional behavior is a lifelong process that residents must commit to during their training. A professionalism policy, which employs a point system, has been instituted in our programs and may be a novel tool to promote awareness and underscore the merits of the professionalism competency.